Effect of Creative Movement and Occupational Therapy as a Community-Based Rehabilitation Program for Post Stroke Elderly at Puskesmas Gresik - Alfianti, Khalifatus Zuhriyah; Istiroha, Istiroha; Basri, Ahmad Hasan; Khomilia, Crysant Ayu Sufi; Malia, Ilkha (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
ABSTRAKBackground: Stroke remains a leading cause of disability among older adults, often resulting in impaired motor abilities and a diminished quality of life. This study aimed to evaluate the impact of combining Creative Movement Therapy (CMT) and Occupational Therapy (OT) on motor function and quality of life among post-stroke elderly individuals in Gresik District, Indonesia.Methods: A quasi-experimental study with a pretest–posttest control group design was conducted from August to September 2025 at Puskesmas Alun-Alun Gresik. The control group (n = 35) received conventional rehabilitation, while the intervention group (n = 35) participated in combined CMT and OT sessions for four weeks, lasting 45–60 minutes each. Motor function was assessed using the Fugl-Meyer Assessment (FMA), and quality of life was measured using the Stroke-Specific Quality of Life (SS-QOL) scale.Results: Participants in the intervention group achieved significantly higher mean ranks for both FMA (46.00) and SS-QOL (43.61) compared to the control group (25.00 and 27.39, respectively; p < 0.05).Conclusion: The integration of Creative Movement Therapy and Occupational Therapy provides an effective, community-based rehabilitation strategy that holistically enhances motor function and overall quality of life among post-stroke elderly individuals